Transformational Leadership Analysis Of Village Apparatus Work Motivation At Asembagus Village Office - Kholifah Juliarta; Miftahus Surur; Irma Noervadila (Journal of International Multidisciplinary Research, 2023)
This study aims to analyze the transformational leadership of the motivation of village apparatus work at the Asembagus village office. Transformational leadership is a leadership concept that focuses on developing and empowering subordinates through inspirational vision, high motivation and the establishment of interpersonal relationships. This research method uses qualitative techniques with data collection techniques through observation and interviews with village officials and village heads at the Asembagus village office. This type of research uses qualitative descriptive research because it collects information about the status of an existing problem. By using qualitative descriptive, it aims to better understand the problem more deeply. The results of this study show that transformational leadership has an influence on increasing the motivation of village officials at the Asembagus village office.